Representasi Visual Rumah dalam Film sebagai Refleksi Simbol Budaya, Identitas dan Kekuasaan - Prasetio, Valentina Marvella; Sujatmiko, Guguh (SPACEPRO: Product Design Jurnal, 2024)
This research analyzes the symbol of the house from the film "Ngeri-ngeri Sedap," which represents family dynamics, traditions, and intergenerational conflicts. This research explores how the houses in this film can symbolize the cultural myths contained within, such as the role of parents, social pressure, and the importance of preserving traditional values. The method used in this research is qualitative analysis with a focus on the visual elements of the house and the meanings created from those representations in Batak Culture. The results of this study show that the houses in this film can represent patriarchal authority, protection, and the conflict between tradition and modernization. The house here is not just a backdrop, but a symbol for reflecting cultural conflicts, identity, and power. This research supports the use of semiotics in understanding the cultural symbols contained within and recommends further research using patriarchal theory to deepen visual analysis.